PLANNING AND IMPLEMENTATION OF INSTITUTIONAL PROJECT REPOSITORY FOR AIKTC - KAZI TABISH ABDULSAEED,; KHAN AFTAB TAHIR,; BHATKAR YASIR NAZIR, (International Journal of Innovations in Engineering Research and Technology, 2021)
Many institutions are adopting institutional repositories to gather and preserve their intellectual works. Institutional Project Repositories is developed primarilyfor assembling, conserving and distributive the scholarly yield of Data. This data assists in sharing and learning of information. For setup of the associate Institutional project Repositoryand coming up with new strategies withthe need of present goal and scope. It becomes difficult to maintain and preserve the final year projects and related documents from the normal system. The primary goal of the Project repository is to preserve the final year project of all the department of AIKTC(Anjuman I Islam Kalsekar Technical Campus). The System handles the documents and the related data of the final year project on the server of the institute. Project repository increasesthe security of accessible files through updated authentication protocols and storage specifications. With the help of different web technologies & pattern matching algorithm, user can access the project that is done by the previous year students. In this project we are doing the enhancement of the already exist repository of our institute. This System is a web-based application through which our user will upload the project on the server of our institute. These uploaded projectscan be accessible to the student of AIKTC.